2011
DOI: 10.1093/europace/eur390
|View full text |Cite
|
Sign up to set email alerts
|

Novel indexes of heterogeneity of ventricular repolarization in subjects with early repolarization pattern

Abstract: Individuals with ER display an increased TDR that may be related to an increased arrhythmic risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…189, 242 The presence of co-existing Brugada ECG pattern (J waves in V1-V3) or short QT intervals in subjects with ER also suggests a more malignant nature. 243, 244 …”
Section: Risk Stratification Of Patients With Ersmentioning
confidence: 99%
“…189, 242 The presence of co-existing Brugada ECG pattern (J waves in V1-V3) or short QT intervals in subjects with ER also suggests a more malignant nature. 243, 244 …”
Section: Risk Stratification Of Patients With Ersmentioning
confidence: 99%
“…38,39 Patients with early repolarization do not seem to display significantly higher inducibility in comparison to those without early repolarization. 38,39 Patients with early repolarization do not seem to display significantly higher inducibility in comparison to those without early repolarization.…”
Section: Risk Stratification Of Vf In Patients With Ersmentioning
confidence: 96%
“…39 In addition, benign early repolarization is associated with a significantly shorter QTc interval, whereas malignant early repolarization is associated with a significantly longer QRS duration. In contrast, the malignant form of ERS, involving horizontal/descending ST-segment variation, is associated with older age and increased ECG signs of coronary artery disease.…”
Section: Early Repolarization: Benign or Malignant?mentioning
confidence: 99%
“…In contrast, horizontal ER in the inferior leads persisted in 29% of cases. Haïssaguerre et al commented that exercise consistently reduced or eliminated ER 2 in ERS, whereas Letsas et al 30 also showed that ER disappeared at peak exercise in 44 out of 47 healthy individuals with ER but neither commented on differences between ascending and horizontal ER. Our group has previously shown that horizontal ER is more likely to persist during exercise and was also associated with a history of syncope.…”
Section: Exercise Ecgmentioning
confidence: 99%